PENGARUH PENAMBAHAN EKSTRAK DAUN KETEPENG CINA (Cassia alata L.) TERHADAP PROFIL HEMATOLOGI DARAH AYAM PEDAGING - M. S., ASHARI; WIDODO, E.; SUDJARWO, E. (Majalah Ilmiah Peternakan, 2023)
The research on the utilization of Cassia alata L. leaf extract as a feed additive in broiler feed was aimed at observing the effect of the hematological profile on broiler. Data were analyzed by using analysis of variance (ANO- VA), if there were differences between treatments followed by Duncan’s Multiple Range Test. The treatments used consisted of PO(-) commercial feed (without treatment), PO(+) commercial feed +0.1% Tetracycline, P1 treatment commercial feed +0.4% extract, P2 commercial feed + 0 ,8% extract, P3 commercial feed + 1.2% extract. Variables observed were hematological profiles which included erythrocytes, leukocytes and hemoglobin. The results showed that the addition of Cassia alata L. leaf extract had no significant effect (P>0.05) on the blood hematological profile of broilers consisting of the number of leukocytes, erythrocytes and blood hemoglobin. It can be concluded that the addition of Cassia alata L. leaf extract as a phytobiotic gave results in P2 treatment with a dose of 0.8% capable of producing erythrocytes of 2.81 x 106/mm3, while hemoglobin of 7.64 g/dL and leukocytes of 15.95. x 103/ml.